Antidiabetic and antioxidants activities of Clinacanthus nutans (Burm F.) Lindau leaves extracts - Murugesu, Suganya; Khatib, Alfi; Ibrahim, Zalikha; Ahmed, Qamar Uddin; Uzir, Bisha Fathamah; Nik Yusoff, Nik Mohd Idris; Perumal, Vikneswari; Abas, Faridah; Shaari, Khozirah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Clinacanthus nutans (Acanthaceae) is a local plant consumed as tisane in Indonesia and ‘ulam’ in Malaysia. This plant has been claimed for its ability to prevent many diseases including diabetes. However, the scientific proof on this claim is still lacking. Therefore, the present work study was designed to evaluate the antidiabetic potential and antioxidant capacity of C. nutans leaves extracts using in vitro bioassay tests. The 80% methanolic crude extract of this plant was further partitioned using different polarity solvents namely hexane, hexane:ethyl acetate (1:1, v/v), ethyl acetate, ethyl acetate:methanol (1:1, v/v), and methanol. All the sub-fractions were analysed for antioxidant effect via 2, 2-diphenyl-2-picrylhydrazil (DPPH) scavenging activity, ferric reducing power (FRAP) and xanthine oxidase (XO) assays followed by antidiabetic evaluation via α-glucosidase and dipeptidyl peptidase-IV (DPP-IV) inhibitory assays and glucose uptake experiment. The ethyl acetate fraction showed a good antioxidant potential while the hexane fraction exhibited high α-glucosidase and DPP-IV enzyme inhibition. The hexane fraction also improved glucose uptake in a dose-dependent manner. The present work thus provides an informative data on the potential of C. nutans to be developed as a functional food in preventing diabetes.